Using Triggers Without Projecting Presuppositions. - Cummins, Chris (Topoi: An International Review of Philosophy, 2016)
Presuppositions are capable of projecting from under the scope of operators such as negation, but do not obligatorily do so. This creates a potential difficulty for the hearer of presupposition-bearing utterances, especially given the fact that speaker can use presupposition to convey entirely new information. In this paper, I discuss the potential role of context in resolving this tension, and in particular, I argue that the inferences that are drawn about the current discourse purpose may be materially relevant to the interpretation of potential presuppositions. I also consider some of the implications of this for recent experimental work on presupposition and projection.